2014
DOI: 10.5039/agraria.v9i4a4731
|View full text |Cite
|
Sign up to set email alerts
|

Leaf-surface characterization and the effects of the herbicide saflufenacil on the leaves of weeds

Abstract: Effects of saflufenacil in Merremia aegyptia (Convolvulaceae), Luffa aegyptiaca (Cucurbitaceae) and Mucuna aterrima (Fabaceae -Leguminosae) were analyzed by scanning electron microscopy one day before and after application. Stomatal density, stomatal index and length of the stomatal aperture were determined by imprinting the leaf epidermis. These species showed stomata on the adaxial and abaxial epidermis. M. aegyptia showed paracytic stomata, unicellular tector trichomes on the abaxial surfaces, especially ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
5
0
2
Order By: Relevance
“…The micromorphometric analyses of the leaves regarding stomatal density index of the adaxial and abaxial surfaces and thickness of the adaxial and abaxial epidermis and palisade and spongy parenchyma were performed with the ANATI QUANTI® software (Aguiar et al, 2007). To obtain the stomatal density and index, the epidermisimprinting technique with cyanoacrylate was used, as described by Alves et al (2014).…”
Section: Methodsmentioning
confidence: 99%
“…The micromorphometric analyses of the leaves regarding stomatal density index of the adaxial and abaxial surfaces and thickness of the adaxial and abaxial epidermis and palisade and spongy parenchyma were performed with the ANATI QUANTI® software (Aguiar et al, 2007). To obtain the stomatal density and index, the epidermisimprinting technique with cyanoacrylate was used, as described by Alves et al (2014).…”
Section: Methodsmentioning
confidence: 99%
“…Essa maior espessura foliar pode representar uma barreira física para absorção de herbicidas resultando em menores efeitos fitotóxicos a essa variedade, pois dessa forma uma menor quantidade de herbicida acaba sendo efetivamente absorvida pela planta e consequentemente desencadeando efeito fitotóxicos menos expressivos. Alves et al (2014) relataram que a superfície foliar das plantas, através da presença de célula epidérmicas diferenciadas e/ou presença de tricomas podem afetar a dinâmica de herbicidas pós-emergentes diminuindo sua absorção e os efeitos deletérios da deriva sobre plantas sensíveis, como por exemplo a alface.…”
Section: Resultsunclassified
“…Some researches relative to leaf blade of Luffa species mentioned only the presence of non-glandular trichomes as in L. acutangular (L.) Roxb., L. echinate Roxb., L. cylindrica 38 and L. aegyptiaca. 39 Alves et al 42 described non-glandular and glandular trichomes in L. aegyptiaca and Rus et al 33 in B. alba. Thus, in this work is possible to note the first description about the presence of non-glandular and glandular trichomes in L. cylindrica.…”
Section: Discussion/ Conclusionmentioning
confidence: 99%
“…Thus, in this work is possible to note the first description about the presence of non-glandular and glandular trichomes in L. cylindrica. Alves et al 42 showed that L. aegyptiaca also has an amphistomatic leaf blade, with anomocytic stomata. However, a useful character to distinguish it from L. cylindrica is that L. aegyptiaca presents collenchyma only on the adaxial face of the midrib, while L. cylindrica showed collenchyma in both faces.…”
Section: Discussion/ Conclusionmentioning
confidence: 99%